Aktivitas Antikarsinogenesis Ekstrak Etanol Daging Buah Mahkota Dewa pada Mencit yang Diinduksi 7,12-Dimetilbenz(a)antrasena - YANDI SYUKRI; SAEPUDIN SAEPUDIN (JURNAL ILMU KEFARMASIAN INDONESIA, 2008)
Mahkota dewa (Phaleria macrocarpa Boerl.) was used empirically for treatment of any kind of diseases, including cancer. The aim of this research is to explore the carcinogenesis inhibition effect of mahkota dewa epicarp extract. The effect was examined using 7,12-dimethylbenz(a)anthracene (DMBA) induced new born mice which Were divided into five groups. All groups received 0.25 mg single intraperitoneal injection of DMBA, except group of normal control. The extract was tested onto three different groups of the mice at the age of 28 days which Was separated from their parental with the doses of 6.25 mg, 12.5 mg, and 25 mg for 16 Weeks and one group Was used as negative control. Anticarcinogenic effect of the extract was evaluated after 16 Weeks by observing the histopathology and total number of all types of neoplasm in hepar, kidney, lung, gastric, intestine, and lymphatic tissue. The result showed that the extract at 6.25 mg, 12.5 mg, and 25 mg decreases carcinogenesis event by 50%, 83%, and 100% , respectively, compared with negative control. In conclusion, the dose of 25 mg extract improved several organs carcinogenesis than other dose, and thereby can be developed as a potential anticancer agent.